Export Restrictions in the Field of Artificial Intelligence and Quantum Computing: Justification and Risks – The United States–China Rivalry from a European Union Perspective - Székely, János (European Integration Studies, 2024)
The study aims to elicit the problems posed under international law and, to a lesser extent, under European Union (EU) law by export controls imposed on foundational transformative technologies such as artificial intelligence and quantum information technology in the relations between United States and People’s Republic of China. It examines the notion of export controls and its evaluation under international law, finding that such an evaluation of the legal nature of these measures remains unclear on not only whether these measures may constitute economic coercion but also whether such coercion is prohibited. Further uncertainty persists regarding whether other legal foundations may be identified, which would permit such measures when they affect critical technologies for future development. The study finds that, currently, export controls affecting artificial intelligence and quantum information technology are limited but expanding, thereby creating some urgency in finding legal solutions to counteract their effects. Updating of the EU legal infrastructure, which is not ready to counteract the unintended effects of export controls on the EU, is also found as necessary.